Development of Plantae Taxonomy Garden as A Contextual Learning Resource of Plantae Subject in High School Biology - Hikmah, Nur; Rahayu, Enni Suwarsi; Saptono, Sigit (Journal of Innovative Science Education)
Learning at SMA N 1 Wonotunggal, Batang Regency on the Plantae subject has not used learning resources in the form of taxonomy garden to observe plant characteristics directly. This study aims to analyze the validity, measure the effectiveness, and describe the practicality of plantae taxonomy garden as a contextual learning resource of plant subject. This study was designed using Research and Development approach and ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model which was tested on 30 students. The results showed (1) the validity of the plantae taxonomy garden is valid with an average score of 77.22%; (2) cognitive learning outcomes based on the N-Gain index of 0.76 which is in the high category and means very good in students' science process skills training with an average assessment score of 86.33%; (3) the response to the use of plantae taxonomy garden by students was 92.13% and teachers 93.18%. These results indicate that the plantae taxonomy garden is a valid resource of contextual learning, effectively improves learning outcomes, able to train students' science process skills, and practically used in learning.